How the pendulum swings: conservation as a tool to both reinforce and disrupt colonial systems of oppression - Layden, Tamara J., author; Bombaci, Sara, advisor; David-Chavez, Dominique, advisor; Pejchar, Liba, committee member; Correia, Joel, committee member (Colorado State University. Libraries, 2025)
Elevating Indigenous leadership in conservation science is critical for social and ecological resilience and recovery. However, Indigenous conservation governance is frequently undermined by persistent colonial research standards. In response, calls to implement ethical guidelines that honor Indigenous rights are mounting. Despite this growing movement, most conservation studies continue to follow largely colonial, extractive models, presenting a widening gap between ethical guidelines and practical applications across diverse research contexts. To help bridge this gap and contribute to the development, application, and evaluation of ethics in conservation practice, my dissertation offers: 1) a primer of the histories and contemporary paradigms that continue to hinder justice in conservation research and practice, 2) ethical guidance and relational evaluation attuned to Indigenous and communal conservation contexts, and 3) a case study example of transdisciplinary approaches to wildlife conservation, grounded in relational accountability to Indigenous and communal rights-holders. My dissertation research draws from Indigenous and multicultural values and methodologies that aim to re-center relationships, with outcomes represented through research, story, and art. Through diverse modalities, this body of work seeks to provide an entry point for cultivating a deeper understanding of justice and decolonization in conservation while offering guidance, recommendations, and examples for researchers, scholars, community members, and institutions to reaffirm Indigenous rights and improve relations with Indigenous stewards, thereby strengthening collective conservation visions and futures.
Keywords: conservation; ethics; justice; decolonization; colonialism; Indigenous rights